Qualitative improvement of camel milk date yoghurt by addition of biosynthesized xanthan from orange waste. (July 2019) - Mohsin, Ali; Ni, Hui; Luo, Yanxia; Wei, Yanlong; Tian, Xiwei; Guan, Wenyan; Ali, Muhammad; Khan, Imran Mahmood; Niazi, Sobia; Rehman, Salim-ur; Zhuang, Yingping; Guo, Meijin
Abstract: Camel milk is worldwide known for its profound nutritional value. However, the poor curd formation of camel milk renders low consumer acceptability. In current study, xanthan gum was added in the production process to attain an adequate firmness factor. Further for enhancing consumer acceptability, dates paste was also added. Storage study was performed four times after an elapse of every 7 days to confirm the product quality for corresponding fractions (0.25, 0.5 and 0.75%) of biosynthesized xanthan (BX) and 1% gelatin as control. Moreover, the rheological measurements were performed and the experimental data were assessed by Herschel-Bulkley model. With the addition of BX, the camel milk date yoghurt (CMDY) demonstrated the shear-thinning behavior with pseudoplastic fluid characteristics. The rheological properties of CMDY were significantly improved in correspondence to higher concentration of BX. Relatively, 0.75% of BX addition resulted in the best texture of yoghurt and obtained an average firmness of 445 ± 34.11 g. Furthermore, confocal CSLM and SEM micrographs demonstrated the detail microstructure of all yoghurt samples. Specifically, addition of 0.75% BX in yoghurt sample demonstrated a strengthened (dense) network of casein micelles. Lastly, the addition of 0.75% BX along with 10% dates paste significantly enhanced the sensory characteristics of CMDY. Highlights: Biosynthesized xanthan was used for the production of camel milk date yoghurt. Improvement in the texture and rheology of camel milk date yoghurt. Use of 0.75% biosynthesized xanthan results in the most dense protein network system. Sensory characteristics was enhanced by using biosynthesized xanthan with date paste.